NAVIGATING LEGAL PATHWAYS: ADDRESSING TRANSBOUNDARY ENVIRONMENTAL HARM THROUGH INTERNATIONAL LAW - Muhammad Hamza Zakir; Muhammad Yaseen; Ibrar Ahmad; Dr Rizwana Gul; Muhammad Nauman Zakir (International Journal of Contemporary Issues in Social Sciences, 2023)
Transboundary environmental harm perpetuates a complex web of ecological, social, and diplomatic dilemmas that traverse beyond geopolitical boundaries, underscoring a critical need for adept international legal frameworks. The research embarks on an analytical journey to explore, evaluate, and navigate the international legal pathways available for addressing instances of transboundary environmental harm, pivoting on the axis of international cooperation, accountability, and ecological sustainability. It delves into a myriad of cases where ecological adversities, such as cross-border pollution, deforestation, and biodiversity loss, transcend national frontiers, probing the efficacy, challenges, and gaps in existing international legal frameworks in mitigating, redressing, and preventing environmental harm. The study harnesses a multi-disciplinary lens, intertwining legal analysis with ecological science, international relations, and ethical considerations, aiming to forge a holistic understanding of the interplay between international law and transboundary environmental dynamics. The anticipated findings seek to illuminate the intricacies, successes, and impediments embedded within legal responses to transboundary environmental challenges, aspiring to pave the way for robust, equitable, and effective international legal strategies that safeguard our shared environment and foster harmonious international relations amidst the escalating environmental crises